2016
DOI: 10.1007/s11123-016-0465-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of participation within formal standardization on firm performance

Abstract: Several studies highlight the economic benefits of standards, while the benefit of taking part in standardization remains a rather unexplored mystery to date. In theory, standard setters not only benefit from the possibility to monitor and shape the development of standards but also access a wide range of knowledge sources in the standards committee. Therefore, we investigate how the participation within formal standardization is related to the performance of 1561 German companies. A Cobb-Douglas production fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…Firms cannot benefit as much from defining a technical specification favorable to themselves when their primary purpose is to improve the new product introduction rate. First, formal standards, which are available to all firms, are codified, and unified knowledge about the proper functioning of products are less beneficial for innovation opportunity recognition (Wakke et al, ). Second, the more influence that firms have in standard setting the higher the likelihood of consistency between industry standards and their current technical systems (Leiponen, ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Firms cannot benefit as much from defining a technical specification favorable to themselves when their primary purpose is to improve the new product introduction rate. First, formal standards, which are available to all firms, are codified, and unified knowledge about the proper functioning of products are less beneficial for innovation opportunity recognition (Wakke et al, ). Second, the more influence that firms have in standard setting the higher the likelihood of consistency between industry standards and their current technical systems (Leiponen, ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Turkey's Small and Medium-Sized Industry Development Organization (KOSGEB) supports the implementation of standards and management systems under its General Support programme. 9 The admissible costs also include certification tests, analyses and calibration. In North Macedonia, SMEs can benefit from a voucher scheme operated by the Innovation Fund to support quality infrastructure investments, including implementation of standards and certification.…”
Section: Financial Support For Sme Access To Standardisation Exists Bmentioning
confidence: 99%
“…This combines a system of public and private organisations with the relevant legal and regulatory framework, and the practices needed to support and enhance the quality, safety and environmental soundness of goods, services and processes. In establishing this network, it will be extremely important to pay special attention to SMEs' needs and challenges (UNIDO, 2017 [9]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they argue that firms' absorptive capacity and the competitive intensity of their industry tend to mediate early-mover advantages (Su et al 2015). Sim-ilarly, Wakke et al (2016) used the number of seats at the German Institute of Stan-dardisation as a proxy for participation in standardisation and found that participation in formal standardization is positively related to firm performance in the German manufac-turing sector but not in the service sector. These studies suggest that revisiting the roles of firm characteristics and capabilities can give more insight into firms' decision to be early or late adopters.…”
mentioning
confidence: 99%